10-year trajectory of β-cell function and insulin sensitivity in the development of type 2 diabetes: a community-based prospective cohort study. Issue 1 (January 2016) - Ohn, Jung Hun; Kwak, Soo Heon; Cho, Young Min; Lim, Soo; Jang, Hak Chul; Park, Kyong Soo; Cho, Nam H
Summary: Background: The relative contributions of β-cell function and insulin sensitivity in the pathogenesis of type 2 diabetes are not fully understood. We investigated the longitudinal change in β-cell function and insulin sensitivity in the development of diabetes and the role of genetic variants in deterioration of glucose tolerance. Methods: We followed up 4106 participants with normal glucose tolerance (NGT) from the Korean Genome and Epidemiology Study with oral glucose tolerance tests every 2 years for 10 years. We estimated pancreatic β-cell function with the 60 min insulinogenic index (IGI60 ) and insulin sensitivity with the composite (Matsuda) insulin sensitivity index (ISI). We investigated the association of 66 known type 2 diabetes genetic variants with risk of prediabetes or diabetes and impaired β-cell function and insulin sensitivity. Findings: During 10 years of follow-up, 1093 (27%) of 4106 participants developed prediabetes and 498 (12%) participants developed diabetes. Compared with participants who remained NGT, those who progressed to diabetes had a lower IGI60 (unadjusted data 5·1 μU/mmol [95% CI 0·5–56·1] vs 7·9 μU/mmol [0·5–113·8]; p<0·0001) and lower ISI (unadjusted data 8·2 [2·6–26·0] vs 10·0 [3·2–31·6]; p<0·0001) at baseline. Participants who had NGT at 10 years showed a decrease in ISI (adjusted data 10·1 [9·9–10·3] vs 7·4 [7·3–7·6]; p<0·0001) but a compensatory increase in IGI60 (adjusted data 6·9 μU/mmol [6·5–7·2] vs 11·7 μU/mmol [11·2–12·1]; p<0·0001) compared with baseline. By contrast, participants who developed diabetes showed a decrease in ISI (adjusted data 8·4 [8·0–8·7] vs 3·0 [2·8–3·2]; p<0·0001) but no significant compensatory increase (p=0·95) in IGI60 . A genetic variant near the glucokinase gene (rs4607517) was significantly associated with progression to prediabetes or diabetes (hazard ratio 1·27, 1·16–1·38; p=1·70 × 10 −7 ). Interpretation: Decreased β-cell function, which might be determined partly by genetic factors, and impaired β-cell compensation for progressive decline in insulin sensitivity are crucial factors in the deterioration of glucose tolerance. Funding: South Korean Ministry of Health & Welfare.